دور القيادة التحويلية في تحقيق الأهداف الاستراتيجية الفلسطينية - عبد القادر منصور, منصور; رجب القانوع, عبد اللطيف (University of Eloued جامعة الوادي, 2016)
هدف هذا البحث الى الكشف عن دور القيادة التحويلية في تحقيق الاهداف الاستراتيجيه للشعب الفلسطيني، والوقوف على مدى اهمية وكفاة القيادات التحويلية الناشطة في التنظيمات الفلسطينية ، واتبع الباحثان المنهج الوصفي التحليلي مستخدمين طريقة المسح الشامل لجميع قيادات الصف الاول والثاني والثالث في التنظيمات الفلسطينية الناشطة في قطاع غزة والمقدر عددهم بــ (191) قائدا لعام 5201-2014م، في حين بلغت عدد الاستبيانات المستردة (161) استبانة بما نسبته (84.3%) من مجتمع الدراسة. ومن أهم النتائج التي توصل إليها البحث : وجود فروق بين حماس وفتح لصالح حماس، وبين حماس والجهاد الاسلامي لصالح حماس، وبين حماس والجبهة الديمقراطية لصالح حماس فيما يتعلق بتحقيق الاهداف الاستراتيجيه الفلسطينية. وكذلك قدم البحث توصيات هامة منها : العمل على تبني السلوك القيادي التحويلي من قبل القيادات السياسية الفلسطينية وذلك من خلال اعداد وتنفيذ برامج تدريبية لاكساب القادة المهارات المطلوبة نظراً لاهمية ودور القيادة في تحفيز المرؤوسين واثارة حماستهم وتوليد الٍاحساس لديهم مما يدفعهم لبذل اقصى جهد ممكن لتحقيق الاهداف الإستراتيجية الفلسطينية. Abstract: This research aimed to clears the importance of transformational leadership of the Palestinian leadership in Palestinian organizations, and determines the level of efficiency of the Palestinian leadership in the practice of transformational leadership. This research follows the researcher descriptive analytical method , the research sample consisted comprehensive survey of all first , second and third grade of leaders in the Palestinian factions in the Gaza Strip and the estimated (191) commander of 2014-2015 , (the administrative offices of the Palestinian organizations) , and the number of questioners recovered (161) questionnaire equivalent to (84.3%) of the study population . There were no significant statistical differences about the relationship of transformational leadership dimensions. And achieving the strategic goals of the Palestinian people due to personal variables , there are difference between (Hamas ) and (Fatah) is to (Hamas), and between (Hamas) and (Islamic Jihad) , is to (Hamas) and between (Hamas) and (Democratic front) is to (Hamas) , in the Palestinians strategic objectives . As well as the search clears important recommendations, including: must provide the Palestinian political leaders of required skills to help them to achieving their goals, by the preparation and implementation of training programs for the leaders
The Role of Transformational Leadership in Achieving the Palestinian Strategic Goals
مجلة رؤى المجلد السادس العدد الأول
Keywords: قيادة التحويلية ، أهداف استراتيجية; Transformational leadership, Strategic Goals. (JEL) Classification : O15, O32.